Analisis Ekonomis, Efisiensi, Dan Efektivitas Anggaran Belanja Pada Kantor Pertanahan Kabupaten Lampung Selatan Tahun 2019-2023 - Riva Ameliya; Darwin Warisi; Siti Khoirina (CV. Ulil Albab Corp, 2024)
The objective of this study was to understand the economical, efficient, and effective implementation of the state budget in government institutions. The data source used in this research is the 2019 – 2023 budget Realization Report, obtained from the Kantor Pertanahan Kabupaten Lampung Selatan. This research uses economic, efficiency, and effectiveness analysis. The research result show that the economic level in the 2019 -2023 budget utilization is an average of 107,63% , which is included in the uneconomic criteria. The efficiency level in achieving the realization of the 2019 – 2023 budget is an average of 94,16%, which is included in the less efficient criteria. The level of effectiveness in achieving the realization of the 2019 – 2023 budget is an average of 107,63%, which is included in the very effective criteria. Thus, the state budget must be economical, efficient, and effective and must continue to be improved.